The Influence of Dominant Local Actors in Villages Financial Management - Fauzia Gunadi, Hanifah Firda; Sjaf, Sofyan; Kolopaking, Lala M. (Departement of Communication and Community Development Sciences, Faculty of Human Ecology, 2020)
Based on a sociological perspective, problems in village financial management are not only in administrative problem but structural problem, which is an intervention from the government, so that access to village financial management is only owned by a handful of people. It has implications for the community participation space so the village development is not in accordance with the real hopes and needs of the village community. This study aims to identify local people who control village financial management and measure the influence index of these actors in carrying out their respective roles in Purwabakti Village and Sukadamai Village in Bogor Regency. The research was conducted using mixed methods The results showed that there were six dominant local actors in village financial management. Five of the six actors are village government officials who can be used as village secretary, village treasurer and chairman of the LPM, while one other actor is the head of the TPK Lapang for infrastructure development from the community. Based on the average value of the influence index of each actor, it can be concluded that the economic capital of the actor is the most important capital to be able to influence the community in the village with the rural characteristic, while the capital of moral actors is the most important capital to influence the community in teh village with the semi-urban characteristic. Actors in semi-urban villages also showed that their educational background and interaction with outsiders contribute to carrying out a structural role in the village.